Aligning fiscal policy with ESG objectives enhancing domestic biomass utilization for Indonesia’s energy transition - Desipradana, Sinar Timur; At Tamimi, Abdul Hakim (WIM Solusi Prima, 2026)
This study examines how fiscal policy can be aligned with Environmental, Social, and Governance (ESG) objectives to strengthen domestic biomass utilization in Indonesia, using palm kernel shells (PKS) as a focal case. Indonesia’s power system remains structurally coal-heavy, while biomass use in 2024 was still limited relative to coal consumption; at the same time, PLN’s biomass co-firing and REC programs show that transition instruments already exist but remain supplementary rather than system-shaping. Adopting a qualitative, policy-oriented case study design based on documentary analysis, the study compares Indonesia’s domestic biomass framework with Japan’s policy-backed biomass import regime. The findings suggest that PKS allocation is driven less by physical scarcity than by incentive asymmetry: Japan’s FIT-linked biomass certification system creates stable demand and sustainability certainty for imported PKS, while Indonesia’s fiscal and tax instruments remain broader, less targeted, and less directly tied to measurable output. The study conceptualizes this gap as ESG–Fiscal Decoupling, referring to the disconnect between sustainability commitments and the fiscal signals needed to change firm-level behavior. It argues that domestic biomass utilization would be strengthened by output-based tax incentives, better certification support, and tighter linkage between fiscal policy and carbon-pricing logic. The contribution of this paper lies in connecting biomass allocation, tax policy, and ESG transition design within a single analytical framework for Indonesia’s energy transition.